Stability Measurement of Dual Banking System in Indonesia: Markov Switching Approach - Zahra, Siti Fatimah; Ascarya, A; Huda, Nurul (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2018)
Various macro and microeconomic shocks that occur during this time suggest the potential for financial instability. This study attempts to analyze the influence of macro and microeconomic variables of the dual banking stability in Indonesia and compares the stability level of both banking system by using two similar stability measurement models namely the Z-score and Banking Stability Index. The method used in this is a Markov Switching VAR. The results of this study described through two analyze: First, the calculation index of financial stability with Z-score and BSI. Second, results of Markov-Switching prove that the sharia banking system has a higher level of stability compared to the conventional banking system. It means sharia banking is more stable than conventional ones.DOI: 10.15408/aiq.v10i1.5867